Premedication Does Not Influence the Incidence of Infliximab Infusion Reactions in Pediatric Patients with Inflammatory Bowel Disease—A Single Center Case–Control Study - Szymanska, Edyta (J Clin Med, 2021)
Background: Infusion reactions (IRs) are the most common adverse events (AEs) of infliximab (IFX) treatment in patients with inflammatory bowel disease (IBD). Prophylactic premedication (PM) with corticosteroids or antihistamines prior to IFX infusions has been used in clinical practice, but its efficacy is not known. The aim of this study was to assess the influence of steroid PM on IR incidence in pediatric patients with IBD receiving IFX. Methods: We performed a case–control study that included pediatric patients with IBD receiving IFX. Patients were divided into four subgroups according to the agent and PM they received: Remicade (original drug) + PM, and two biosimilars—Reshma +/− PM, and Flixabi—PM. At our site, until 2018, PM with steroids was used as a part of standard IFX infusion (PM+); however, since then, this method has no longer been administered (PM−). IRs were divided into mild/severe reactions. Differences between subgroups were assessed with the appropriate chi-square test. Multivariate logistic regression was used to assess associations between PM and IR incidence, correcting for co-medication usage. Results: There were 105 children (55 PM+, 44 male, mean age 15 years) included in the study who received 1276 infusions. There was no difference between the PM+ and PM− subgroups, either in incidence of IR (18.2% vs. 16.0% of patients, p > 0.05) or in percentage of infusions followed by IR (2.02% vs. 1.02% of infusions, p > 0.5). The OR of developing IR when using PM was 0.34, and the difference in IRs ratio in PM+ and PM− patients was not statistically significant (95% CI, 0.034–1.9). There were 11/18 (61.1%) severe IRs (anaphylactic shock) reported in all patients (both PM+ and PM−). Conclusion: At our site, the incidence of IR was low, and PM did not decrease the incidence of IR in pediatric patients with IBD receiving IFX. These results indicate that PM with steroids should not be a standard part of IFX infusion to prevent IR.